Postpartum sexual activity and contraceptive use among women in a southwest health facility Osun State Nigeria - Oke, Oluwaseyi F.; Oke, Elizabeth O.; Owonikoko, Kola M.; Oladiran, Taiwo W.; Adewole, Adefisoye O.; Adu, Temitope S.; Ojedokun, Samson A.; O. Orji, Ernest (International Journal Of Community Medicine And Public Health, 2022)
Background: The post-partum period presents a risk in unwanted/unplanned conception and often frustrating desire for contraceptive. This study aimed to determine the factors enhancing resumption of sexual intercourse, contraceptive usage and barriers to timely uptake of family planning methods. Methods: This cross-sectional study was conducted among 340 women within 3 to 16 weeks postpartum. Structured questionnaires adopted from similar studies were administered within three months. Statistical analysis was performed using the statistical package for the social sciences (SPSS) version 21. Results: 62.6% (213) of women resumed sexual activity with a mean time of 11.37 weeks±8.85 postpartum. More than one-third 37.6% (80) did so within puerperium and husbands in 78.4% (167) initiated sex. About 50% (107) were on modern contraceptives, whereas only 39.3% (42) were on contraception before their first postpartum sexual experience. Conclusions: There was high rate of resumption of sexual intercourse early in postpartum with less attention on contraceptive usage mostly due to misconceptions surrounding fertility return. Sexual and contraceptive education after delivery is necessary for both mothers and their husbands.